ISOLASI DAN KARAKTERISASI MORFOLOGI KOLONI BAKTERI ASOSIASI ALGA MERAH (RHODOPHYTA) DARI PERAIRAN KUTUH BALI - Aninditia Sabdaningsih; Anto Budiharjo; Endang Kusdiyantini (Jurnal Akademika Biologi, 2013)
Kutuh Beach in Bali is an area established as the Minapolitan algae with a high diversity. Microorganisms associated with marine organisms, usually have secondary metabolites that can be used as a source of drugs, antibiotics, enzymes, and cosmetics. The aimed of this research was to isolate and characterize colony morphology of bacteria associated with red algae based on colony morphology. Seven bacteria were isolated from three samples of red algae that were Kappapycus alvarezii, Gelidiella acerosa and Eucheuma spinosum. The isolates had pigmentation of beige, white and orange. Based on Gram's staining, seven isolates were Gram positive with bacilli and cocci in shape. Keywords : associated bacteria, morphological colony, pigmentation, red algae